GRANGER CAUSALITY APPROACH TO THE CONFIRMATION OF POST-COVID 19 KEYNESIAN TWIN-DEFICIT HYPOTHESIS IN NIGERIAN ECONOMY - EZE, TITUS CHINWEUBA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2023)
One of the recent critical post COVID 19 challenges being witnessed across the globe especially among the developing countries, Nigeria inclusive, has been the increasing cases of deficit financing aimed at providing economic and social overheads in view of insufficient private investment in these countries. Thus, while the developed countries are re-strategizing on how to contain this menace, the developing countries, Nigeria in particular, with her agrarian economy as the major employer of labor, is currently facing a monumental food crisis caused by a combination of socio-political imbalance in the system. This paper was aimed at investigating the extent to which changes in budget deficits predicts changes in current account balance in Nigeria using time-series data spanning from 1980 to 2022. The methodology adopted for the study was multiple regressions. The regression results show that at 5 per cent levels of significance and relevant degrees of freedom, changes in budget deficits (Bd) have a positive and significant long-run impact on current account balance (CAB) in Nigeria. Furthermore, a short-run negative relationship between budget deficit and export was also established, thus confirming the presence of twin deficits hypothesis in post COVID 19 Nigerian economy. Moreover, the result of the system equations confirmed the existence of a causal relationship between budget deficits and current account balance in Nigeria. The recommendation was that government should adopt fiscal management actions aimed at minimizing borrowing and capable of reducing fiscal deficits that often result in a large amount of transfer payments and questionable additional budget expenses in Nigeria.